Direct visualization of reactant transport in forced convection electrochemical cells and its application to Redox Flow Batteries - Rubio-Garcia,J; Kucernak,ARJ; Charleson,A (Electrochemistry Communications, 2018)
A novel, simple and low cost electrochemiluminescence imaging method for monitoring mass transport phenomena in a redox flow battery-like system is presented. Luminol solutions were pumped through a flow field (FF) with a given design. At the flowfield/electrode interface light is emitted upon dye oxidation allowing direct visualization of channels, U-bends and regions of poor wetting. Image analysis allows direct visualization of reactant distribution and poor mass transport through tortuous materials. These results were compared with the experimental performance of an allvanadium redox flow battery with different FFs as a function of flow and good correlation achieved.